Normalization of informatisation parameter on airfield light-signal bar at flights in complex meteorological conditions - Попов, П.В. (Proceedings of National Aviation University (archive), 2005)
The technique of maintenance of the set level of flights safetivness is developed by normalization of informatisation parameters functional groups of light-signal lightings at technological stages of interaction of crew of the airplane with the airfield light-signals bar at flights in a complex weathercast conditions.